PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T. (The Accounting Review, 1949)
Abstract The article presents information about professional examinations for a department for students of accounting. The following problems were prepared by the Board of Examiners of the American Institute of Accountants and were presented as the first half of the May, 1949 Certified Public Accountant examination in accounting practice. Candidates were required to solve all problems in four and a half hours. A suggested time schedule is also given in the article. Some problems are the condensed balance sheets of company A, B and C were prepared as of December 31, 1948. The stock of Company C was acquired by Company B on January 31, 1947. Since that date Company C has had total earnings of $28,400 and paid cash dividends of $40,000. Company B has credited all dividends received to its income account. Company A acquired the stock of Company B on December 31, 1948. Students were asked to prepare the journal entries necessary for the preparation of a consolidated balance sheet of Company A and subsidiaries as of the close of business December 31, 1948. Show all supporting computations in good form.